2005
DOI: 10.1007/s00774-005-0631-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in girls and boys at different pubertal stages: relation with gonadal steroids, bone formation markers, and growth parameters

Abstract: Puberty has a key role in bone development. During puberty, several nutritional and hormonal factors play a major role in this process. The aim of this study was to determine the changes in areal bone mineral density (BMD), gonadal steroids, bone formation markers, and growth parameters in healthy Turkish pubertal girls and boys at different pubertal stages. In additional, we aimed to detect the relationship between BMD, sex steroids, and growth parameters, and to reveal the most important determinant of BMD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
108
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 39 publications
15
108
3
6
Order By: Relevance
“…This is similar to other studies in healthy children that showed significant correlations between bone mass and BTMs [20][21][22][23]. A study by Jürimäe et al [21] showed significantly negative associations between BTMs and lumbar spine BMD, which remained significant after adjustment for age and pubertal stages.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to other studies in healthy children that showed significant correlations between bone mass and BTMs [20][21][22][23]. A study by Jürimäe et al [21] showed significantly negative associations between BTMs and lumbar spine BMD, which remained significant after adjustment for age and pubertal stages.…”
Section: Discussionsupporting
confidence: 89%
“…Recruitment should thus be restricted to children in pubertal stages II to IV according to established Tanner stages [174][175][176]. Notably, statistically significant differences were found in changes of LS-aBMD z-scores when comparing prepubertal (Tanner stage I) to pubertal children (Tanner stages II-V) in our study (p=0.02).…”
Section: Strengths and Limitationsmentioning
confidence: 72%
“…In support of these assumptions, several studies demonstrate a positive correlation between serum estrogen and BMD during puberty in females (16,49,57,59), thus concluding that estrogen must be a major stimulator of bone development during this period of rapid growth. Although several studies make this conclusion, there is no direct evidence that estrogen is the key molecule responsible for the increased bone accretion and increased GH during puberty.…”
mentioning
confidence: 82%
“…In terms of the potential messenger molecules that regulate the surge in the GH/IGF axis, it is well accepted that the pubertal surge in estrogen is responsible for increased GH, which in turn stimulates IGF-I and thus bone growth. Several studies demonstrate increased growth and GH with estrogen treatment during puberty or a positive correlation between bone development and increased pubertal growth, which are associated with increased estrogen (7,19,28,32,37,47,57). If estrogen is indeed the major factor involved in regulating the pubertal surge in GH/IGF axis and increased bone accretion, then we would expect OVX prior to the pubertal growth period to result in decreased rise in IGF-I levels, bone size, and bone mass; however, this was not the case.…”
Section: Estrogen Is Not a Key Mediator Of The Gh/igf Surge During Pumentioning
confidence: 99%